MAKNA BIJAKSANA PADA TOKOH ZAINUDDIN DALAM FILM TENGGELAMNYA KAPAL VAN DER WIJCK (SEMIOTIKA ROLAND BARTHES) (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
The purpose of this study is to determine the representation of the wise meaning found in the character Zainuddin in the film "Tenggelamnya Kapal Van Der Wijck". The focus of the research on the meaning of wisdom on the character Zainuddin in the film "Tenggelamnya Kapal Van Der Wijck". This research is an analysis of media texts using the semiotic analysis model of Roland Barthes. Data collection techniques in this study use documentation, observation, and library research. The data analysis technique used is that data in the form of signs including narrative and visuals will be analyzed using the semiotic concept of Roland Barthes, namely denotation or understanding of what is in the image and the connotation or meaning behind the image. The results show that the meaning of wisdom is represented by the character Zainuddin both in language and iconic among them; (1) Zainuddin maintains a polite attitude and does not let out his anger. (2) Zainuddin maintains the meaning of true love by proposing to Hayati without disclosing the many possessions that he has. (3) connecting the ties that were previously cut off. (4) The sincerity of a Zainuddin to forgive and forget all the bad treatment Asiz and Hayati had on him. (5) Zainuddin's attitude of giving them a lift and freedom. (6) Zainuddin's wise sentence "Your fall is not the beginning of your sorrow but the beginning of your resurrection, never let sadness and sorrow enter you" as a life lesson. Research implications (1) This research is conducted so that the public understands the wisdom shown by Zainuddin in the film and can apply this wise attitude in everyday life. (2) When watching a film, the audience should not be passive so that they can be more critical in accepting the message the film wants to convey. (3) This research is expected to be a reference for future researchers on semiotic analysis and about the world of film.